Sleep duration pattern among workers in a tertiary institution. - , Azmawati Mohammed Nawi; , Jonathan Lamit; , Nor Farahana Razali; Ong, Li Chin; , Naim Syahidah Zulkafli; , Norfazilah Ahmad (Universiti Kebangsaan Malaysia, 2014)
Sleep has played a very important role in maintaining our health with good living quality therefore the aim of this study is to determine the pattern of sleep duration,especially short sleep and its associated factors among workers in a tertiary institution.A cross-sectional study was conducted from January until May 2012 among 128 randomly selected Universiti Kebangsaan Malaysia Medical Centre(UKMMC) staffs. Data was collected using a guided standardized data sheet which consist of three sections; (1):sociodemographic &socioeconomic, (2):lifestyle and,(3): anthropometric measurement and sleep diary. Data entry and analysis were done using Statistical Package for Social Sciences (SPSS)version 20.0.Majority of the staffs had normal sleep duration (67.2%) followed by short sleep duration (26.6%) and long sleep duration (6.3%). Simple logistic regression analysis indicated that late night snacking was significantly related to short sleep (cOR=3.47, 95% CI: 1.12, 12.23, p=0.048).Adequate sleep is important to maintain one’s health. Steps can be taken to limit late night snacking in order to improve the sleep pattern in this study population.